The Prevalence of Cardiovascular Abnormalities in Thyrotoxicosis A Cross Sectional Study (Journal of Medicine, 2015)
Background: In this Cross sectional study over a period of one year, conducted in the Division of Cardiology, Dept. of Medicine, Govt. Medical College Hospital Jammu, a total of 50 cases were studied for cardiovascular abnormalities occurring in thyrotoxicosis.Aims: We investigated the prevalence and clinical importance of cardiovascular abnormalities in patience with thyrotoxicosis.Settings and Design: This is a cross sectional study conducted over a period of one year in a tertiary care hospital offering specialty and super specialty including cardiology. We studied 50 cases of whom 11 were males and 39 were females. The study covered age group with a range of 16 years to 85 years.Methods and Material: All newly diagnosed cased of thyrotoxicosis were included in the study and were evaluated on a protocol which includes: history, general physical examination, cardiovascular examination and investigation: bio chemical profile, hormonal assay, chest radiography, twelve lead electrocardiogram (ECG), Echocardiography (ECHO) (M-Mode/2 dimensional/Colour Doppler).Statistical Analysis: Descriptive analysis including calculation of percentages as deemed fit for qualitative variables. For quantitative variables, mean and standard deviation were calculated and reported.Results: 50 patients (Mean [+/- SD] age, 45.7 yrs, range 16-85 yrs; 78% females) were included. Weakness and fatigability was present in every patient (100%), followed by palpitation, shortness of breath and weight loss (94%). We found ventricular hypertrophy (40%), congestive heart failure (CHF) (36%), cardiomegaly (24%), arrhythmias (24%) and bundle branch block (18%) of the patients.Conclusion: Cardiovascular abnormalities in thyrotoxicosis should never be over looked, prognosis and outcome of the heart disease depends on early institution of treatment and control of the hormone levels.J MEDICINE July 2015; 16 (2) : 69-72